Deciphering the impact of whey protein powder storage on protein state and powder stability. (August 2022) - Paul, A.; Gaiani, C.; Cvetkovska, L.; Paris, C.; Alexander, M.; Ray, C.; Francius, G.; EL-Kirat-Chatel, S.; Burgain, J.
Abstract: Whey protein concentrate powders can be strongly affected by storage conditions inducing both chemical and structural protein modifications. In the present work, a combination of different storage conditions were evaluated, leading to the evaluation of 6 different batches that were chosen in order to evaluate the impact of the following parameters: storage temperature, storage duration and storage heat load (°C.days). In each set the relative humidity was maintained at 70%. To estimate the impact of the three parameters, whey protein lactosylation, denaturation and aggregation were followed. It was shown that the highest temperatures (60 vs 55.5 °C and 41 vs 36 °C) led to greater protein modification, whereas the duration (17 vs 14 days and 33 vs 30 days) and the total heat load (low vs high C°.days) did not affect protein modification. Lactose content is known to be an important parameter for powder browning. Here, we show that if lactose content is crucial for the level of initial process induced browning of the powder, the additional browning that occurs during storage is mostly independent of lactose content. In addition, during storage, detected lactosylated proteins were found to be inversely proportional to powder browning indicating the occurrence of advanced Maillard reaction steps ( e.g. dicarbonyl and AGEs formation and production of melanoidins). Protein aggregates contained both β-lactoglobulin and α-lactalbumin and were mostly formed by non-disulphide covalent bonds. Interestingly, despite protein structure being strongly impacted, good powder rehydration properties were obtained for the studied conditions. Graphical abstract: Image 1 Highlights: Whey powder functionality is not impacted by storage. Maillard-induced protein modification is repeatable between powder productions. Initial protein lactosylation content drives powder aging. Browning during storage is not related to lactose content.